High-Dose-Rate Brachytherapy as Monotherapy for Low- and Intermediate-Risk Prostate Cancer. Oncological Outcomes After a Median 15-Year Follow-Up - Behmueller, Manuel; Tselis, Nikolaos; Zamboglou, Nikolaos; Zoga, Eleni; Baltas, Dimos; Rödel, Claus; Chatzikonstantinou, Georgios (Frontiers in Oncology, 2021)
Introduction: To evaluate the oncological outcome of high dose rate (HDR) brachytherapy (BRT) as monotherapy for clinically localised prostate cancer (PCA). Material and methods: Between January 2002 and February 2004, 141 consecutive patients with clinically localised PCA were treated with HDR-BRT monotherapy. The cohort comprised 103 (73%) low-, 32 (22.7%) intermediate- and 6 (4.3%) high risk patients according to D’Amico classification or 104 (73.8%) low-, 24 (17.0%) intermediate favourable-, 12 (8.5%) intermediate unfavourable- and one (0.7%) very high risk patient according to National Comprehensive Cancer Network (NCCN) one. Patients received four fractions of 9.5 Gy delivered within a single implant up to a total physical dose of 38 Gy. Catheter-implantation was transrectal ultrasound-based whereas treatment planning CT-based. Thirty-three patients (23.4%) received ADT neoadjuvantly and continued concurrently with BRT. Biochemical relapse-free survival (BRFS) was defined according to the Phoenix Consensus Criteria and genitourinary (GU) / gastrointestinal (GI) toxicity evaluated using the Common Toxicity Criteria for Adverse Events version 5.0. Results: Median age at treatment and median follow-up time was 67.2 and 15.2 years, respectively. Twenty-three (16.3%) patients experienced a biochemical relapse and 5 (3.5%) developed distant metastases, with only one patient dying of PCA. The BRFS was 85.1% at 15 years and 78.7% at 18 years. The corresponding overall survival, metastases-free survival, and prostate cancer specific mortality at 15- and 18-years was 73.9% / 59.1%, 98.3% / 90.6%, and 100% / 98.5% respectively. Late grade 3 GI and GU toxicity was 4.2% and 5.6% respectively. Erectile dysfunction grade 3 was reported by 27 (19%) patients. From the prognostic factors evaluated, tumor stage (≤T2b compared to ≥T2c) along with the risk group (low-intermediate vs. high) when using the D’Amico classification but not when the NCCN one was taken into account, correlated significantly with BRFS. Conclusion: Our long-term results confirm HDR-BRT to be a safe and effective monotherapeutic treatment modality for low- and intermediate risk PCA.